In-situ diagnostic supported tailoring of spatial and temporal pulse shaping for materials processing - Jenne, M.; Kumkar, M.; Grossmann, D. G.; Zimmermann, F.; Kleiner, J.; Flamm, D.; Kaiser, M.; Nolte, Stefan (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
The high peak power of ultrashort laser pulses enables the processing of transparent materials by inducing absorption nonlinearly. There are already a variety of applications in the field based on volume or surface absorption. Spatial beam shaping offers high potential, for example by applying Bessel-like beams for single pulse full thickness modification in cutting applications. Temporal shaping the pulse or applying bursts of pulses adapted in amplitude and interval is a further option to localize and dose the energy deposition. An alternative option for scaling is processing at elevated repetition rates. This typically results in accumulation effects, often not desired, sometimes useful or even necessary for several applications. Learning about the complex interplay of the effects relevant for ultrashort pulse laser processing of transparent materials is crucial for the development of advanced industrial applications. Pump-probe diagnostics have proven to be a powerful tool for analyzing the laser matter interaction of spatially shaped beams with high temporal resolution. By extending this to broader range of temporal parameters of the pump, including flexible burst operation, combined with unlimited delay range of the probe and integrated optional polarization microscopy, high speed camera and observation during translation of the workpiece, the setup is suitable to analyze effects on different temporal and spatial scales in a single setup. The potential of this modular experimental system is demonstrated by analyzing multi pulse focusing of Gaussian and Bessel-like beams into glass.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Beam shaping; Materials processing; Nonlinear absorption; Pump probe; Ultrafast